The Effect of Online Discovery Learning in Google Classroom Environment on Students' Scientific Literacy Skills - Priadi, Median Agus; T. Marpaung, Rini Rita; Yolida, Berti; Safitra, Shalsadinda Dewi (Jurnal Pendidikan MIPA, 2022)
This research aimed to determine the effect of the discovery learning models using a google classroom to develop the scientific literacy abilities. The sample of this research is tenth grade students of science 2 and science 3 groups which are selected through purposive sampling technique. The data are analyzed statistically with an independent sample t-test. The average results of the N-gain scientific literacy ability of the experimental class (0.45 ± 0.11) with medium category and the control class (0.29 ± 0.14) with low category. The average percentage for student presentations is 83.75%, while the learning implementation observation sheet has a 94.4%. The results showed that there is a significant effect of using online discovery learning in google classroom environment towards the improvement of scientific literacy skills of tenth graders students in ecosystems topics.Keywords: discovery learning, scientific literacy, google classroom.DOI: http://dx.doi.org/10.23960/jpmipa/v23i1.pp316-326